Comparative Study of Local and International Marketing Strategies for Cosmetic Brands: A Case Study of 3CE - Fan, Xinyue (Transactions on Social Science, Education and Humanities Research, 2024)
Korean cosmetic products have a significant global presence, and the study of Korean cosmetic products can help to understand the size of the market, growth trends Consumer preferences, which can be enlightening in developing local and overseas marketing strategy development and market forecasting and seeking business development across borders. This paper takes the Korean 3CE brand as an example and focuses on its 4ps of local and overseas marketing for comparative analysis and finds that the brand has successfully utilised product differentiation in the market, capturing market vacancies, packaging giveaways, and unique beauty technology, as well as launching marketing policies in different countries to adapt to the local aesthetic preferences and fashion trends, to gain a unique marketing advantage in the market. It is also important to understand the reasons for success and the challenges faced both at home and abroad, in order to provide corresponding practical suggestions for the future development of the brand.